1994
DOI: 10.1073/pnas.91.15.7257
|View full text |Cite
|
Sign up to set email alerts
|

The H1A histone variant is an in vivo repressor of oocyte-type 5S gene transcription in Xenopus laevis embryos.

Abstract: Previous in vitro transcription studies have pointed to the importance of histone Hi for repression of oocyte-type SS genes of Xenopus laevis. It has been previously reported that in development up to the earl gasrula ge, Xenopuis embryos contain a large pool of the maternal histone Hi variant HiM but are vrtually devoid of histone H1A, HiB, 7257The publication costs of this article were defrayed in part by page charge payment. This article must therefore be hereby marked "advertisement" in accordance with 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
53
1

Year Published

1996
1996
2004
2004

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(62 citation statements)
references
References 28 publications
8
53
1
Order By: Relevance
“…The H1M (B4) protein is present in the embryonic chromatin up to the midblastula transition, when it starts to be diluted out by the de novo synthesis of somatic histone H1 (24). The progressive replacement of embryonic H1M (B4) by adult H1 in the chromatin is responsible for the specific repression of the oocyte 5S rRNA genes in the gastrula embryo (7,38), in agreement with recent genetic evidence that histone H1 variants of Tetrahymena are also involved in gene-specific rather than global transcriptional regulation (61). A role for H1M (B4) in gene regulation is further supported by the correlation observed between the incorporation of H1M (B4) and the acquisition of transcriptional competence in somatic nuclei following chromatin remodeling in frog egg extracts (26).…”
Section: Discussionmentioning
confidence: 99%
“…The H1M (B4) protein is present in the embryonic chromatin up to the midblastula transition, when it starts to be diluted out by the de novo synthesis of somatic histone H1 (24). The progressive replacement of embryonic H1M (B4) by adult H1 in the chromatin is responsible for the specific repression of the oocyte 5S rRNA genes in the gastrula embryo (7,38), in agreement with recent genetic evidence that histone H1 variants of Tetrahymena are also involved in gene-specific rather than global transcriptional regulation (61). A role for H1M (B4) in gene regulation is further supported by the correlation observed between the incorporation of H1M (B4) and the acquisition of transcriptional competence in somatic nuclei following chromatin remodeling in frog egg extracts (26).…”
Section: Discussionmentioning
confidence: 99%
“…Preferential binding of histone H1 has been described for the AT-rich DNA sequences of the SAR (17) as well as the AT-rich flanking sequences of the oocyte-type 5S RNA gene of Xenopus laevis (39), leading to the specific repression of the Xenopus oocyte 5S rRNA gene (6,16). In order to determine if histone H1 could also preferentially bind to the AT-rich DNA sequence present on the upstream region of the IFN-␤ promoter, we carried out a series of photofootprinting analyses of the muIFN-␤ promoter in the presence and absence of histone H1.…”
Section: High-affinity Binding Of the Hmgi Protein To The Upstream Atmentioning
confidence: 99%
“…This finding indicates that linker histones facilitate the in vitro folding of nucleosomal arrays but are not required for chromatin and chromosome assembly. In somatic cells of Xenopus, histone H1 was shown to function as a developmentally regulated gene repressor acting specifically on the set of embryonic 5S RNA genes (4,22,46) and mesoderm-specific genes (53). In the case of 5S RNA genes, molecular studies indicated that the repressive effect of histone H1 is related to differential nucleosome positioning (38,49).…”
mentioning
confidence: 99%